Functional lung volume mapping with perfusion Single-Photon Emission Computed Tomography scan for radiotherapy planning in patients with locally advanced nonsmall cell lung cancer. Issue 10 (October 2020) - Follacchio, Giulia Anna; D'Urso, Pasqualina; Cassese, Raffaele; Ferrara, Carla; Bulzonetti, Nadia; Monteleone, Francesco; Musio, Daniela; Liberatore, Mauro; Tombolini, Vincenzo
Abstract : Objectives: Radical chemotherapy-radiotherapy represents the standard treatment for locally-advanced nonsmall cell lung cancer (NSCLC). Conventional radiotherapy achieves limited local tumor control, but dose escalation to the primary tumor is prevented by radiotherapy-induced toxicity. The aim of this study was to evaluate feasibility of tailored intensity-modulated radiotherapy (IMRT) planning based on lung single-photon emission computed tomography (SPECT) perfusion data and to compare functional and conventional dose-volume parameters. Methods: A total of 21 patients were prospectively enrolled. Patients underwent IMRT treatment with 2 Gy/fraction (median total dose of 60 Gy). Lung perfusion SPECT images were acquired before radiotherapy and 3 and 6 months after radiotherapy completion. SPECT and planning computed tomography images were co-registered using MIM-MAESTRO software with 3D-PET Edge algorithm. Lung volumes were defined anatomically as total lung and functionally as total not functional lung and total functional lung. Dose-volume histograms were calculated using QUANTEC constraints [mean lung dose (MLD)<20 Gy, V20 <20%]. For each patient, conventional and functional radiotherapy plans were generated and compared. Results: A total of 19 of 21 patients with NSCLC were included (mean age 66 years, 11 stage IIIA, 8 stage IIIB), 12/19 patients completed the 6-months follow-up. A significant reduction of mean V20 was observed in functional radiotherapy planning compared to conventional plan (405.9 cc, P < 0.001). Mean MLD was also lower in the SPECT-based plans, but the difference was not statistically relevant (0.8 Gy, P = 0.299). G2 radiation pneumonitis was observed in two patients. Conclusions: Functional radiotherapy planning allowed to decrease functional lung irradiation compared to conventional planning. The possibility to limit radiotherapy-induced toxicity could allow us to perform an effective dose-escalation to target volume.